Lymphopenia and immunoglobulin deficiency in adult patients with a Fontan circulation. (3rd October 2022) - Possner, M; Bonassin Tempesta, F; Santos Lopes, B; Meier, L; Babic, D; Attenhofer Jost, C; Greutmann, M
Abstract: Background: Patients with a functionally univentricular heart and a Fontan palliation are prone to a wide range of extra-cardiac complications. Lymphopenia and immunoglobulin deficiency are insufficiently characterized in this population. Purpose: The aim of this study was to analyze prevalence and associations of lymphopenia and immunoglobulin deficiency in a cohort of adult Fontan patients. Methods: Ninety-five consecutive patients with a Fontan circulation that were seen at our institution between 2011 and 2021 were screened. Laboratory results and clinical characteristics were extracted from the patient's charts. Results: Fifty-five patients (47% male) underwent evaluation of lymphocyte and/or immunoglobulin subpopulations at a mean age of 28.9±9.7 years. Baseline characteristics are depicted in the Table. Seven patients (7/55, 12.7%) had immunoglobulin G (IgG) levels below the lower limit of normal (i.e. <7.0 g/l). Patients with IgG deficiency had a higher prevalence of protein-losing enteropathy (43% versus 4%, p=0.001). Fifteen patients (15/52, 28.8%) had lymphocyte counts below the lower limit of normal (i.e. <850/μl). Lymphocyte counts and lymphocyte subpopulations were comparable in groups with and without protein-losing enteropathy. There was a moderately positive correlation between absolute lymphocyte counts and IgG levels (r=0.301, p=0.032). In a subgroup of 24 patients that underwent liver biopsy, there was no difference in terms of absolute lymphocyte counts and immunoglobulin subpopulations in patients with a low (i.e. 1–2) and high (i.e. 3–4) congestive hepatic fibrosis score. Conclusion: IgG deficiency is present in 13% of patients with a Fontan circulation and seems to be associated with the presence of protein-losing enteropathy. Lymphopenia is more common and occurs in a quarter of all patients with a Fontan circulation; however, its etiology is likely more complex and multifactorial. Funding Acknowledgement: Type of funding sources: None.